2004
DOI: 10.1111/j.1475-6773.2004.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Coding Response to a Case‐Mix Measurement System Based on Multiple Diagnoses

Abstract: Objective. To examine the hospital coding response to a payment model using a casemix measurement system based on multiple diagnoses and the resulting impact on a hospital cost model. Data Sources. Financial, clinical, and supplementary data for all Ontario short stay hospitals from years 1997 to 2002. Study Design. Disaggregated trends in hospital case-mix growth are examined for five years following the adoption of an inpatient classification system making extensive use of combinations of secondary diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 11 publications
1
25
0
1
Order By: Relevance
“…Coders then travel to hospitals and re-abstract patient charts on-site. Separate studies of Canadian discharge data have shown consistent results [12][13][14] that are comparable to international results [15].…”
Section: Methodssupporting
confidence: 79%
“…Coders then travel to hospitals and re-abstract patient charts on-site. Separate studies of Canadian discharge data have shown consistent results [12][13][14] that are comparable to international results [15].…”
Section: Methodssupporting
confidence: 79%
“…The peer review organization system for coding behavior and DPC creep will be in demand, just like in other countries that are already Fig. 2 Hospital mortality (per 1,000 cases) and number of comorbidities and complications, stratified by treatment group (medical or surgery) and major diagnostic category utilizing those kinds of case-mix classification systems [16][17][18][19]. Third, there was a limitation of coding slots in the DPC dataset, whereby only seven secondary diagnoses (four comorbidities and three complications) could be listed.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the clinical information reported from Ontario hospitals has been studied [13][14][15] and hospital response to cost weights has been observed in Ontario [3] and resultant bias in cost weights estimated [16]. The accuracy and adherence to micro-costing standards by hospitals is evaluated on an annual basis by the Ontario Ministry of Health and Long-Term Care, although it is known that averaging departmental costs over broader groups of patients introduces attenuation bias in the cost weights [17].…”
Section: Datamentioning
confidence: 99%
“…However, this assumption is not always tenable, borne out by experience in many jurisdictions. For example, dramatic changes over time in the mix of patients within resource groups has been observed when hospitals have optimized coding practices in order to maximize reimbursement under case based payment systems [1][2][3].…”
mentioning
confidence: 99%